2013
DOI: 10.1039/c3an01129a
|View full text |Cite
|
Sign up to set email alerts
|

The characterization of the concentration of the single-walled carbon nanotubes in aqueous dispersion by UV-Vis-NIR absorption spectroscopy

Abstract: Current and future applications of single-wall carbon nanotubes (SWCNTs) depend on the dispersion of the SWCNTs in aqueous solution and their quantitation. The concentration of SWCNTs is an important indicator to evaluate the dispersibility of the surfactant-dispersed SWCNTs suspension. Due to the complexity of the SWCNTs suspension, it is necessary to determine both the total concentration of the dispersed SWCNTs and the concentration of individually dispersed SWCNTs in aqueous suspensions, and these were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 15 publications
(19 reference statements)
0
11
1
Order By: Relevance
“…Although this study showed a detection limit of MWCNT as 0.39 μg/mL, a previous study suggests that the limit of detection for MWCNT using a UV-Vis spectrophotometer is 0.025 μg/mL [ 10 ], which is more sensitive than any of the metal-labelling methods like Ni-labelling, which showed a 0.1 μg/mL limit of detection [ 27 ], and PTA, which showed 0.2 μg limit of detection [ 9 ]. In comparison with this study, the lower detection limit of MWCNT performed by Zhang et al [ 10 ] could be due to the difference in the physicochemical properties such as length, diameter, and dispersibility [ 28 30 ]. Furthermore, the use of UV-Vis spectrophotometer is available to other types of nanomaterials such as metal oxides (Table S 3 , see Supporting Information).…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Although this study showed a detection limit of MWCNT as 0.39 μg/mL, a previous study suggests that the limit of detection for MWCNT using a UV-Vis spectrophotometer is 0.025 μg/mL [ 10 ], which is more sensitive than any of the metal-labelling methods like Ni-labelling, which showed a 0.1 μg/mL limit of detection [ 27 ], and PTA, which showed 0.2 μg limit of detection [ 9 ]. In comparison with this study, the lower detection limit of MWCNT performed by Zhang et al [ 10 ] could be due to the difference in the physicochemical properties such as length, diameter, and dispersibility [ 28 30 ]. Furthermore, the use of UV-Vis spectrophotometer is available to other types of nanomaterials such as metal oxides (Table S 3 , see Supporting Information).…”
Section: Discussioncontrasting
confidence: 67%
“…Data are expressed as mean ± SEM and n = 4. The detailed numeric data are presented in Tables S1 and S2 (see Supporting Information) agglomerates, which was broadly used in the process of nanomaterial dispersion [30,33,34]. Briefly, CNM powders were dispersed in DW containing 30% v/v heatinactivated FBS and sonicated using a bath sonicator (Saehan Sonic, Seoul, Korea) to break up agglomerates.…”
Section: Dispersion Of Cnmsmentioning
confidence: 99%
“…The establishment of a relationship between certain UV-Vis wavelengths to dispersion quantification in aqueous CNT suspensions has proved difficult due to material impurities and environmental and other uncontrollable factors during the sonication process. From our review, we found that the best results were obtained when a wide range of wavelengths were considered simultaneously to quantify dispersion (e.g., resonance ratios and normalized widths) [56,82,83]. Another result from our review is that the bands around the peak absorbance wavelengths are critically important in determining the dispersion of the CNT suspension.…”
Section: Discussionmentioning
confidence: 83%
“…Therefore, these authors related the resonance ratio with the fraction of individual nanotubes in the final suspension. A similar strategy was employed by Yang et al [90], who used absorbance and resonance ratio measurements to demonstrate that the region 300-600 nm is the most suitable to evaluate of the total concentration of dispersed CNTs in suspension, while the region below 800 nm is the most appropriate to evaluate the concentration of individually dispersed nanotubes. The last of the three approaches, i.e., the use of complete spectra or multiple wavelengths, was employed by Grossiord et al [91], who demonstrated that the exfoliation process of aggregates and bundles of carbon nanotubes in aqueous solution by sonication could be monitored by UV-vis measurements.…”
Section: Ultraviolet-visible and Near Infrared Absorption Spectroscopiesmentioning
confidence: 99%
“…Despite the fact that certain UV-vis wavelengths have been selected for direct evaluation of the concentration of CNTs dispersed in an aqueous liquid phase, the best results were obtained when a wide range of wavelengths was considered to calculate resonance ratios and normalized widths [89,90]. Moreover, it should be noted that the majority of these techniques have been applied to SWCNTs obtained using the CoMoCAT synthesis method (which gives rise to a remarkably narrow distribution of tube diameters).…”
Section: Ultraviolet-visible and Near Infrared Absorption Spectroscopiesmentioning
confidence: 99%